2000
DOI: 10.1111/j.1479-828x.2000.tb03164.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of pregnancies complicated by pre‐gestational diabetes mellitus

Abstract: Pregestational diabetes mellitus (DM) is associated with adverse fetal and maternal outcomes. Studies suggest that optimal control of diabetes before and during pregnancy minimises these risks. There are few recent reviews of outcomes of pregnancies complicated by DM in Australia. Ninety-three pregnancies in women with DM at our hospital since 1989 were identified. We collected data for maternal age, type of diabetes, duration of therapy, complications of diabetes, maternal complications of pregnancy and fetal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 23 publications
3
33
0
2
Order By: Relevance
“…This study has confirmed the findings of other studies, that the incidence of major congenital malformations for women with pregestational diabetes is in the order of 5–10%[1–3]. The incidence was similar for women with Type 1 and Type 2 diabetes, but gestational diabetes was associated with a much lower incidence of major congenital malformations (1.4%).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study has confirmed the findings of other studies, that the incidence of major congenital malformations for women with pregestational diabetes is in the order of 5–10%[1–3]. The incidence was similar for women with Type 1 and Type 2 diabetes, but gestational diabetes was associated with a much lower incidence of major congenital malformations (1.4%).…”
Section: Discussionsupporting
confidence: 90%
“…Pregestational diabetes, whether Type 1 or Type 2, is associated with a two to eight‐fold increase in the rate of major congenital defects in the fetus [1–6]. This association is thought to be secondary to the teratogenic effect of hyperglycaemia in early pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Research across Australia and internationally has established that there are low rates of preconception care among women with T2DM [3,19,20]. A recent crosssectional survey of healthcare professionals within the NT Diabetes In Pregnancy (DIP) Partnership highlighted that few women with T2DM are seen for preconception counselling [21].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies (Table 1) 4,5, [7][8][9][10][11][12][13][14][15][16][17][18][19] report that up to 62% of women with type 1 diabetes received PC, whereas < 36% of women with type 2 diabetes received PC. In studies by Gunton et al, 4,5 the rate of women with type 1 diabetes having received PC improved significantly over time (from 18.9 to 62.5%), but a downward trend was noted in the rate for women with type 2 diabetes (from 52.6 to 36.4%). With the rising rates of obesity and type 2 diabetes in the United States and throughout the world, 6 there is a rising number of women of childbearing age with type 2 diabetes.…”
Section: Background and Clinical Problem: Preconception Counselingmentioning
confidence: 94%
“…Gunton et al 4,5 found significantly lower rates of cesarean section in women who had PC (13.6 vs. 48%, P < 0.05; 31.6 vs. 72.7%, P = 0.0295), and GarciaPatterson et al 10 found a significantly higher rate of cesarean section in women who had PC (71 vs. 54.9%, P < 0.05). Willhoite et al 8 also reported a higher cesarean section rate in women who received PC (81 vs. 66%) that did not reach statistical significance.…”
Section: Evidence-based Clinical Decision Makingmentioning
confidence: 96%